Suriname : 2005 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report, 2006)
Suriname's 2005 Article IV Consultation reports that economic activity has strengthened reflecting increased mining output and investment. The principal short-term challenge for Suriname is to maintain disciplined fiscal and monetary policies, especially to contain the inflation impact of the increase in domestic fuel prices. Over the medium term, the priority will be to entrench a consistent macroeconomic policy framework and advance critical public sector reforms to minimize the vulnerability to exogenous shocks and improve the competitiveness of nonmining sectors.